Output-Based Aid in Chad : Using Performance-Based Contracts to Improve Roads - Hartwig, Tim; Mumssen, Yogita; Schliessler, Andreas (World Bank, Washington, DC, 2012)
Despite Chad's recent debut as an oil exporter, its people rank among the world's poorest. Large parts of the country are left in extreme isolation by the lack of a backbone road network that is passable year-round. To tackle the poor internal integration, the government formulated the National Transport Program in 1999. And to address the need for sustainable road maintenance, it started a pilot project that moves from traditional input-based planning and contracting of maintenance, to the more output-based approach known as performance-based maintenance and management of roads (PMMR). The International Development Association (IDA) has provided funds for the project as part of its efforts to support an efficient and sustainable transport infrastructure - essential for promoting economic growth and development, and for achieving the Millennium Development Goals. A primate operator has been contracted to provide road services. Results so far are encouraging, and the Government plans to expand the share of the road network covered by PMMR contracts. The PMMR arrangement is being replicated in Sub-Saharan Africa, including Burkina Faso, Cape Verde, Madagascar, and Tanzania.